Evaluasi Sistem Proteksi Listrik Kantor Bupati Landak (Faculty of Engineering, Universitas Tanjungpura, 2012)
Abstract- Electrical protection systems in Landak Regent office is inadequate and not well integrated. The analysis shows that external protection of Landak Regent office consisting of a single lightning rod installed on the building, has not been able to protect whole of the office building. Landak Regent office building length is 161,50 meters, while the calculation of lightning protection radius obtained by 73,46 meters. The results shows that there is part of Regent office building that have not been protected by the lightning rod or outside the cone incline of 7,29 meters on the left side and 7,29 meters on the right side, so we need to add another electrostatic lightning rod by changing the electrostatic lightning rod installation position on the edge of the left side and the right side of the building or increase the height of the lightning rod. Lightning rod conductor installed on Landak Regent office was meet the standart of PUIL Indonesia published in the year 2000 and meet the standard of PUIPP Indonesia which using BC 50 copper wire without insulation. The grounding resistance value is 7,8 ?, so that can be declared not good. Solution for a small grounding resistance value is by increasing the depth of the earth electrode, increasing the number of electrodes and parallelize those electrode implanted. Internal protection in the form of overvoltage protection on the computer network (LAN) LPSE room currently not ideal, because the protection which installed only using UPS. To improve the reliability of lightning protection at computer network (LAN) LPSE room, overvoltage arresters should be installed in the line before it goes into the equipment. Keywords: Lightning, External Protection, Internal Protection, Protection Radius